CALCULATE ENERGY BALANCE IN POWER BOILERS USING BIOMASS TO DETERMINE ENERGY REQUIREMENTS - Imaniah Sriwijayasih; Eky Novianarenti; Priyo Agus Setiawan; Kgs Muhammad Abubakar; Sri Haryati; Bayu Wiro Karuniawan; Prativi Khilyatul Auliya; Sryang Tera Sarena (Surabaya State Polytechnic of Shipbuilding, 2024)
Boilers function to produce hot water or hot steam from combustion products to be converted as energy. Steam is used to drive turbines to produce electrical energy, apart from that steam is also used for heating. The boiler fuel uses biomass in the form of tree bark, namely acacia mangium. The aim of this study is to find out whether the process running in the Power boiler is good or not, it can be seen from its efficiency, so that the energy balance calculation is carried out on the Power boiler itself. Therefore, a study is needed to determine the energy balance of the unit. From the heat balance calculation, the heat data for producing steam was 1924,927,054 kcal, the latent heat of vaporization was 5732,620,038 kcal and the feed water heat was 11156296.65 kcal. So from the calculations obtained we can find out the energy balance in the boiler and the resulting Supply Steam Consumption